Improving Air Quality by Nitric Oxide Consumption of Climate-Resilient Trees Suitable for Urban Greening - Zhang, Jiangli; Ghirardo, Andrea; Gori, Antonella; Albert, Andreas; Buegger, Franz; Pace, Rocco; Georgii, Elisabeth; Grote, Rüdiger; Schnitzler, Jörg-Peter; Durner, Jörg; Lindermayr, Christian (Frontiers in Plant Science, 2020)
Nitrogen oxides (NOx), mainly a mixture of nitric oxide (NO) and nitrogen dioxide (NO2), are formed by the reaction of nitrogen and oxygen compounds in the air as a result of combustion processes and traffic. Both deposit into leaves via stomata, which on the one hand benefits air quality and on the other hand provides an additional source of nitrogen for plants. In this study, we first determined the NO and NO2 specific deposition velocities based on projected leaf area (sVd) using a branch enclosure system. We studied four tree species that are regarded as suitable to be planted under predicted future urban climate conditions: Carpinus betulus, Fraxinus ornus, Fraxinus pennsylvanica and Ostrya carpinifolia. The NO and NO2sVd were found similar in all tree species. Second, in order to confirm NO metabolization, we fumigated plants with 15NO and quantified the incorporation of 15N in leaf materials of these trees and four additional urban tree species (Celtis australis, Alnus spaethii, Alnus glutinosa, and Tilia henryana) under controlled environmental conditions. Based on these 15N-labeling experiments, A. glutinosa showed the most effective incorporation of 15NO. Third, we tried to elucidate the mechanism of metabolization. Therefore, we generated transgenic poplars overexpressing Arabidopsis thaliana phytoglobin 1 or 2. Phytoglobins are known to metabolize NO to nitrate in the presence of oxygen. The 15N uptake in phytoglobin-overexpressing poplars was significantly increased compared to wild-type trees, demonstrating that the NO uptake is enzymatically controlled besides stomatal dependence. In order to upscale the results and to investigate if a trade-off exists between air pollution removal and survival probability under future climate conditions, we have additionally carried out a modeling exercise of NO and NO2 deposition for the area of central Berlin. If the actually dominant deciduous tree species (Acer platanoides, Tilia cordata, Fagus sylvatica, Quercus robur) would be replaced by the species suggested for future conditions, the total annual NO and NO2 deposition in the modeled urban area would hardly change, indicating that the service of air pollution removal would not be degraded. These results may help selecting urban tree species in future greening programs.